1987
DOI: 10.3109/10715768709069768
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Formation of Reactive Oxygen Intermediates in Phagocytic Cells

Abstract: Viruses cause disease by a wide variety of mechanisms. These include the impairment of differentiated host cell functions and the killing of infected cells. The latter is referred to as cytopathic effect and is exemplified by Polio virus infection where paralysis results from the loss of neurons killed by the virus. Host immune response as a factor contributing to disease is evident in the skin rashes in measles and rubella. Virus-immune complexes occur in many infections and may be associated with glomerulone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 28 publications
0
67
0
Order By: Relevance
“…This was first shown for the Sendai virus model and mouse splenocytes, which enhance the production of FR in response to contact with the virus, not only intact, but also inactivated by ultraviolet irradiation [49]. Later the increase of oxidative activity in cells leading to their death was shown for many viruses, both RNA and DNA genomic [44,50,52].…”
Section: Suppression Of Virus Reproduction Due To Antioxidant Activitymentioning
confidence: 90%
“…This was first shown for the Sendai virus model and mouse splenocytes, which enhance the production of FR in response to contact with the virus, not only intact, but also inactivated by ultraviolet irradiation [49]. Later the increase of oxidative activity in cells leading to their death was shown for many viruses, both RNA and DNA genomic [44,50,52].…”
Section: Suppression Of Virus Reproduction Due To Antioxidant Activitymentioning
confidence: 90%
“…Therefore, the induction of LPO in the liver is not mediated directly by the cytochrome P-450 system. Several studies have suggested that an overreaction of the host's immune system to influenza virus involves free radical generation outside the liver (Oda et al 1989;Peterhans 1987Peterhans , 1997aPeterhans , 1997b. Some mechanisms responsible for acceleration of LPO in target organs during the course of infection have been discussed: activation of neutrophils and macrophages to produce superoxide free radicals and hydrogen peroxide, which normally are involved in the killing of microbes (Oda et al 1989;Peterhans 1997aPeterhans , 1997bSchwarz 1996), activation of proteases and subsequent acidosis (Goto and Kawaoka 1998), activation of superoxide-generating enzyme xanthine oxidase (Oda et al 1989;Akaike et al 1990Akaike et al , 1996Peterhans 1997aPeterhans , 1997b, virus-induced increase in free iron with subsequent iron-induced LPO (Schwarz 1996), activation of lipoxygenases (Antal et al 1986), and accumulation of nitric oxide and nitrosyl complexes (Peterhans 1997a;Murphy et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The acute form of influenza was shown to result in a release of several biogenic amines (Han et al 2000), a production of interferon (Samuel 1991;Cox and Hughes 1999), an activation of nitric oxide synthase and xanthine oxidase (Oda et al 1989;Akaike et al 1996;Peterhans et al 1997a;Murphy et al 1998), a stimulation of respiratory burst in phagocytic cells (Peterhans 1987(Peterhans , 1997a and an accumulation of lipid peroxidation products in blood and target organs (Oda et al 1989;Schwarz 1996;Peterhans 1997aPeterhans , 1997bMurphy et al 1998;Mileva et al 2000). The liver is one of the most widely investigated targets for influenza.…”
Section: Introductionmentioning
confidence: 99%
“…The physiologically controlled ROS levels play a key role in the hosts' counter attack to invading microbes [10&11]. Previous studies reported that oxidative stress caused by Paramyxoviruses ISSN: , which permits unrestricted use and Influenza [12] and Hepatitis B virus, Sendai virus, cytomegalo virus and HIV [13, 14&15] was implicated to the dramatic increase in the levels of ROS. Although a few nonspecific antiviral drugs are being used to control the NDV infection, continuous usage of these synthetic drugs cause development of resistance in virus.…”
Section: Sophora Interruptamentioning
confidence: 99%
“…The Phenolics from the roots of Sophora interrupta Bedd were extracted according to the method of Singh et al ( [2]. 100gm of Sophora interrupata Bedd root powder was soaked in 500 mL of Methanol-water (80:20v/v) and subjected to ultrasonication (Branson Sonifier, USA) at 60% duty cycles for 15 min at 4 0 C followed by centrifugation at 7500 rpm for 15 min.…”
Section: Extraction Of Phenolicsmentioning
confidence: 99%